2021
DOI: 10.1021/acsami.1c13166
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Orientation of the Aromatic Spacer Cation in Bilayer Perovskite Solar Cells through Spectroscopic Techniques

Abstract: Slowing the degradation of perovskite-based solar cells (PSCs) is of substantial interest. We engineered the surface by introducing a hydrophobic overlayer on a 3-dimensional perovskite using fluorinated or nonfluorinated aryl ammonium cation spacers. The placement of a fluoroarene cation allows the formation of a bilayer structure i.e., layered/3-dimensional perovskites. By doing so, the surface hydrophobic character increases notably by the virtue of perfluorinated benzene moiety. The fabricated devices ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…S9, ESI†). The extracted built-in-potentials ( V bi s) of Spiro-OMeTAD and ZnPc dimers ZnPc 1 , ZnPc 2 , and ZnPc 3 are 1031 mV, 833 mV, 1014 mV, and 914 mV, respectively, 2 following the V oc trend. We noted increased recombination resistance for the ZnPc 3 based PSC as compared to ZnPc 1 , ZnPc 2 , and Spiro-OMeTAD by electrochemical impedance spectroscopy (EIS) measurement 37 made under dark conditions (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…S9, ESI†). The extracted built-in-potentials ( V bi s) of Spiro-OMeTAD and ZnPc dimers ZnPc 1 , ZnPc 2 , and ZnPc 3 are 1031 mV, 833 mV, 1014 mV, and 914 mV, respectively, 2 following the V oc trend. We noted increased recombination resistance for the ZnPc 3 based PSC as compared to ZnPc 1 , ZnPc 2 , and Spiro-OMeTAD by electrochemical impedance spectroscopy (EIS) measurement 37 made under dark conditions (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Halide perovskites are being considered a new paradigm for sustainable energy harvesting owing to their potentially attractive optoelectronic properties, such as high absorption coefficients and long carrier diffusion lengths, tolerance to defects, and the possibility of processing from solutions at low temperatures. [1][2][3] Their application in photovoltaics (PVs) further promises flexibility, light weight, and efficient performances. The performance of perovskite solar cells (PSCs) comparably matches that of mature silicon-based cells (27.6%), measuring power conversion efficiencies (PCEs) of up to 25.7%.…”
Section: Introductionmentioning
confidence: 99%
“…The orientation of molecules is fundamental to the device's performance, and therefore, the perpendicular order of lead and iodine atoms to the PTAA surface can facilitate the nucleation at the perovskite interfaces and will allow effective extraction of charge carriers and lower charge recombination. 14 Additionally, the high hole mobility and electrical conductivity of PTAA will enable high recombination resistance through the fluent transport of the photo-generated charge carriers toward the anode. 51.52 We noted that the Rrec of the PSCs reduces with an increase in applied dc voltage (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…The possible reasons for hysteresis in PSCs are charge accumulation at interfaces, unbalanced charge carrier transport and extraction, ion and vacancy migration, and trap-assisted charge recombination. [12][13][14] Moreover, the presence of defects or traps at the perovskite/charge transport layer interfaces acts as a trapping center for charge carriers, which successively causes non-radiative losses and reduces the lifetime of free-charge carriers, resulting in deterioration of device performance. 15 Such issues can be addressed by developing stable perovskite materials, charge transport layers, and optimized processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Recently, our group also used a thin layer of an aromatic compound called fluoro-phenethyl ammonium iodide (FPEAI) as a passivator over the 3D perovskite, and an optimized concentration of FPEAI (0.3 w v À1 ) exhibited a higher PCE of 20.63% due to reduced nonradiative carrier recombination, and higher stability than the control device. [28] Jiu et al spin coated 1H-Pyrazole-1-carboxamidine hydrochloride (PAH) on the formamidinium lead iodide (FAPbI 3 ) film to passivated defects sites at room temperature. X-ray photoelectron spectroscopy (XPS) and Fourier-transform infrared (FTIR) showed that there is an interaction between PAH and surface Pb ions, reducing the trap states and increasing the device performance.…”
mentioning
confidence: 99%